Gastrojejunocolic fistula: A case report - BJ, Khairussaleh; TH, Kyaw (IIUM Medical Journal Malaysia, 2009)
Benign gastrojejunocolic fistula is mostly due to Bilroth II operations. It typically presents with a triad of feculent vomiting, weight loss and chronic diarrhoea but sometimes the diagnosis is not straight forward. We discuss a case that presented and was investigated as intestinal obstruction however diagnosed with gastrojejunocolic fistula during surgery.